Oral Anticoagulant Therapy and its Control: An International Survey - Lam-Po-Tang, P. R. L. C; Poller, L (Thrombosis and Haemostasis, 1975)
A survey for the International Study Group for Anticoagulant Control has been conducted in which a questionnaire was sent to members in 39 countries. Information based on 37 replies obtained indicated that the most widely used test in oral anticoagulant therapy is the Quick one stage prothrombin estimation. There is a great diversity in the method of reporting prothrombin time results. Percentage activity of normal on the basis of saline dilution curves is the most popular. Only six countries have national or regional systems for anticoagulant control.Recommendations for the therapeutic range of dosage vary widely. The upper limit in one country may be the lower limit in another. In many centres doses of anticoagulant drugs are advocated which elsewhere are considered either inadequate anticoagulation or dangerous overdosage. The variation of therapeutic range may still be considerable even when a standard thromboplastin is available.Data collected from the survey indicates the need for urgent measures to provide a uniform basis of laboratory control of clinical dosage of anticoagulant drugs. Until such measures are implemented it is meaningless to try to compare the efficacy of oral anticoagulant therapy from country to country or even to attempt multicentre trials within national boundaries.